2023
DOI: 10.1007/s11899-023-00688-6
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Marrow Immune Microenvironment in CML: Treatment Responses, Treatment-Free Remission, and Therapeutic Vulnerabilities

Abstract: Purpose of Review Tyrosine kinase inhibitors (TKIs) are very successful for the treatment of chronic myeloid leukaemia (CML) but are not curative in most patients due to persistence of TKI-resistant leukaemia stem cells (LSCs). The bone marrow immune microenvironment (BME) provides protection to the LSC through multidimensional interactions, driving therapy resistance, and highlighting the need to circumvent these protective niches therapeutically. This review updates the evidence for interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…The potential of exosomes as a fluid biopsy for the identification of cancer biomarkers has garnered increasing attention during the past decade. Research like these has shown how critical it is to develop innovative methods for accurately and quickly separating exosomes from bodily fluids with little sample preparation time required [21][22][23][24][25]. Serious problems with purity and more intact performance arise when exosomes are exposed to contaminants and mechanical damage.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of exosomes as a fluid biopsy for the identification of cancer biomarkers has garnered increasing attention during the past decade. Research like these has shown how critical it is to develop innovative methods for accurately and quickly separating exosomes from bodily fluids with little sample preparation time required [21][22][23][24][25]. Serious problems with purity and more intact performance arise when exosomes are exposed to contaminants and mechanical damage.…”
Section: Discussionmentioning
confidence: 99%
“…LSCs reside in the bone marrow immune microenvironment [ 89 ]. This microenvironment provides LSCs with protection against apoptosis, provides resistance to leukemia therapy, and circumvents immune responses [ 90 ]. For example, bone marrow stromal cells can stabilize the β-catenin, which is associated with resistance to tyrosine kinase inhibitors used to treat CML [ 91 ].…”
Section: Effect Of the Hematopoietic Microenvironment On Lscsmentioning
confidence: 99%
“…As a result -via enhancing the metabolic plasticity, pro-survival signaling and proliferation of leukemic cells -the bone marrow cells may favor the persistence and progression of leukemia, including the self-renewal capacities of the malignant progenitor cells (Vianello et al, 2010). Overall, the bone marrow microenvironment is known to contribute to myeloid malignancies and protect CML cells from drug-induced cytotoxicity through various routes of intercellular communication (Chen et al, 2021;Dolinska et al, 2023;Joshi et al, 2021;Kolba et al, 2019;Korn and Méndez-Ferrer, 2017;Le et al, 2020;Pal et al, 2022;Patterson and Copland, 2023). For example, immunosuppression and T-cell exhaustion (Swatler et al, 2022b(Swatler et al, , 2022a are promoted in the presence of leukemic extracellular vesicles (EVs).…”
Section: Introductionmentioning
confidence: 99%